2008
DOI: 10.1080/09603100701222317
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency change, technological progress and productivity growth of private, public and foreign banks in India: evidence from the post-liberalization era

Abstract: This study uses a nonparametric frontier approach to examine the effects of the ownership on the efficiency, efficiency change, technological progress and productivity growth of the Indian banking industry over the period 1998 to 2003. A host of best practice frontiers are constructed relative to which the performance of foreign-owned banks, private-owned banks and public-owned banks operating in India are assessed. The results indicate that foreign banks are significantly more efficient when compared to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…However, in-sample public sector commercial banks exhibited higher Malmquist index than the in-sample private sector banks. Likewise, Rezvanian et al (2008) also used Malmquist index to examine the effects of the ownership on efficiency, efficiency change, technological progress, and productivity growth of the Indian banking industry over the period of 1998-2003 They found that foreign banks were operating significantly more efficient than privately owned and publicly owned banks. Chen et al (2005) employed a non parametric technique to examine the change in the efficiency of 43 Chinese banks between 1993 and 2000 in response to the 1995 banking deregulation.…”
Section: Total Investmentmentioning
confidence: 99%
“…However, in-sample public sector commercial banks exhibited higher Malmquist index than the in-sample private sector banks. Likewise, Rezvanian et al (2008) also used Malmquist index to examine the effects of the ownership on efficiency, efficiency change, technological progress, and productivity growth of the Indian banking industry over the period of 1998-2003 They found that foreign banks were operating significantly more efficient than privately owned and publicly owned banks. Chen et al (2005) employed a non parametric technique to examine the change in the efficiency of 43 Chinese banks between 1993 and 2000 in response to the 1995 banking deregulation.…”
Section: Total Investmentmentioning
confidence: 99%
“…The prominence of private sector banks in an economy is enormous for a number of reasons. The top priority goes to maintain competitive environment in order to be able to provide better customer services and to ensure a sustainable economic development (S. Kumar & Gulati, 2008;Rezvanian et al, 2008). Moreover, globalization effect the privatization of national banking system and boost the private banking sector as an easy access to flourish and growth (Chowdhury & Ahmed, 2009;M.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Private sector banks are of immense need for facilitating the continuity of sustainable economic development (Chowdhury & Ahmed, 2009;Rezvanian, Rao, & Mehdian, 2008). Banks are now offering a wide range of both financial (e.g., deposits, loans, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations